2007
DOI: 10.1007/s10608-006-9087-9
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Focus During Repeated Checking Influences Memory but not Metamemory

Abstract: Compulsive checking may be associated with reduced memory confidence, which results from changes in encoding during the act of repeated checking. It was hypothesized that instructions to focus attention on one's surroundings as well as one's actions during a repeated checking task may attenuate decreases in memory confidence. Prior to a repeated checking task, 64 participants were instructed to focus not only on their actions but also on their surroundings (Peripheral condition), and 66 participants were instr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 43 publications
2
19
1
Order By: Relevance
“…There are at least two distinct possibilities: One is that individuals with OCD have intact access to their subjective states, but meta-cognitive processes such as excessive self-monitoring and self-questioning lead to doubts in regard to these states. This possibility is consistent with studies demonstrating the effects of checking behavior on memory and perception confidence (Ashbaugh & Radomsky, 2007;van den Hout & Kindt, 2003a, b;Radomsky & Alcolado, 2010;Radomsky et al, 2006;Tolin et al, 2001) and with studies that found no real memory deficits in OC individuals other than memory confidence (e.g., Abbruzzese, Bellodi, Ferri, & Scarone, 1993;Ceschi, Van der Linden, Dunker, Perroud, & Bredart, 2003;Foa, Amir, Gershuny, Molnar, & Kozak, 1997;Jelinek, Moritz, Heeren, & Nadar, 2006;Karadag, Oguzhanoglu, Ozdel, Atesci, & Amuk, 2005;Kim et al, 2006;Simpson et al, 2006). The alternative possibility is that inputs from internal states in OCD are attenuated, so that checking and self-questioning only serve to increase doubts that are grounded in a real deficiency in perceiving and experiencing internal states.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There are at least two distinct possibilities: One is that individuals with OCD have intact access to their subjective states, but meta-cognitive processes such as excessive self-monitoring and self-questioning lead to doubts in regard to these states. This possibility is consistent with studies demonstrating the effects of checking behavior on memory and perception confidence (Ashbaugh & Radomsky, 2007;van den Hout & Kindt, 2003a, b;Radomsky & Alcolado, 2010;Radomsky et al, 2006;Tolin et al, 2001) and with studies that found no real memory deficits in OC individuals other than memory confidence (e.g., Abbruzzese, Bellodi, Ferri, & Scarone, 1993;Ceschi, Van der Linden, Dunker, Perroud, & Bredart, 2003;Foa, Amir, Gershuny, Molnar, & Kozak, 1997;Jelinek, Moritz, Heeren, & Nadar, 2006;Karadag, Oguzhanoglu, Ozdel, Atesci, & Amuk, 2005;Kim et al, 2006;Simpson et al, 2006). The alternative possibility is that inputs from internal states in OCD are attenuated, so that checking and self-questioning only serve to increase doubts that are grounded in a real deficiency in perceiving and experiencing internal states.…”
Section: Discussionsupporting
confidence: 92%
“…For example, in the case of the young person with OCD mentioned above, his concentration on rehearsing sentences ironically resulted in poorer understanding of the material, leading to a vicious cycle of further losing confidence in his ability to understand and developing other compensatory proxies, such as counting lines and pages he has read. This notion is in line with the well established finding that repeated checking, which we conceptualize as a proxy for reduced conviction regarding memory and perception, can ironically increase doubts in the relevant memory (Ashbaugh & Radomsky, 2007;van den Hout & Kindt, 2003a, b;Radomsky & Alcolado, 2010;Radomsky, Gilchrist, & Dussault, 2006;Tolin et al, 2001) or perception (van den Hout et al, 2008;van den Hout et al, 2009). Another problem with proxies is that at close examination, they may lose their apparent clarity and engender further substitution.…”
Section: Discussionsupporting
confidence: 87%
“…Repeated mental checking caused slight but significant decreases in memory accuracy for mental but not for physical checks. These results do not replicate initial findings that memory accuracy was not affected by repeated checking (van den Hout & Kindt, 2003a, 2003b; however they are consistent with later work completed in ecologically valid settings (Ashbaugh & Radomsky, 2007;Coles et al, 2006;Radomsky, Gilchrist, et al, 2006). A typical traditional assessment of memory accuracy however (e.g., "Which three knobs did you check on the last trial?")…”
Section: Discussioncontrasting
confidence: 75%
“…Research into the underlying mechanism of obsessional doubt demonstrated that compulsive behaviors, and especially checking, only increase obsessional doubt, leading to a vicious cycle of more checking and more doubting (e.g., Ashbaugh & Radomsky, 2007;van den Hout & Kindt, 2003, 2004. However, not much is known about why obsessional doubts are maintained despite ample evidence that contradicts them.…”
Section: Introductionmentioning
confidence: 99%